Enforcement of fiscal rules: Lessons from the fiscal compact - Martin Larch; Matthias Busse; László Jankovics (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
In 2012, 22 EU countries signed the Fiscal Compact, an intergovernmental agreement aimed at backing EU fiscal rules with national arrangements. The main objective of the Compact was to strengthen compliance. Based on a survey of national independent fiscal institutions, we take a closer look at the correction mechanism, the core of the Fiscal Compact. As the name suggests, the correction mechanism is meant to automatically trigger fiscal adjustment in case public finances deviate from 'the path of virtue'. While design choices vary considerably across countries, a cluster analysis reveals distinct patterns. In particular, better compliance tend to be associated with a superior design of the correction mechanism, higher government efficiency and a stronger media presence of independent fiscal institutions. Economic growth can make up for a less sophisticated design. Additional inferential analysis confirms the link between compliance, design and other relevant valiables. Our survey also indicates that many countries have linked the trigger of the correction mechanism to formal decisions at the EU level rather than to independent assessors at the national level. This choice defeats the original purpose of correction mechanisms, namely to decouple key fiscal policy decisions from political considerations and discretion.
Keywords: E62; H62; H68; H77; 330; Fiscal policy; fiscal governance; budgetary forecasts; correction mechanism; Fiscal Compact; independent fiscal institutions; fiscal councils